MILDLY INCOMPATIBLE ELEMENTS IN PERIDOTITES AND THE ORIGINS OF MANTLE LITHOSPHERE - Canil D. (My University, 2004)
The abundances of the mildly incompatible elements Al, Cr, V, Sc and Yb in more than 1700 mantle peridotite bulk rock analyses are interpreted in the light of a fractional melting model based on experimentally measured partition coefficients (D) and melting reaction stoichiometries. All peridotites examined, irrespective of sample type (abyssal peridotites, orogenic massifs, ophiolites, on/off craton xenoliths), tectonic environment (divergent/convergent/passive margin, intraplate) or the pressure (P) they last equilibrated at in the mantle (plagioclase-, spinel- , or garnet facies), originated as residues at less than 3 GPa, mainly within the spinel-facies. Mantle rocks currently in the garnet facies likely were originally spinel-facies lithosphere underthrust or subducted to greater depths in convergent margins. This view is inescapable even within the widest range of D values employed in the calculations, and is furthermore strengthened when metasomatic effects on the abundances of the mildly incompatible elements in residues are considered. A pressure of origin of below ∼3 GPa for most mantle lithosphere creates difficulties for any model ascribing a significant volume of deep, cratonic mantle roots to plume sub-cretion or any other vertical tectonic mechanism.
Keywords: Mantle; Lithosphere; Peridotite; Melting; Trace element; Geochemistry; Modeling